Teun A. Van Dijk’s Discourse Analysis of Ustadz Firanda Andirja Abidin’s Calendar Messages - Amin, Muliaty; Muh. Said, Nurhidayat; Khairiyyah, Yaumil (Jurnal Mercusuar, 2020)
This study aims to analyze the discourse of Ustadz Firanda Andirja Abidin’s da’wah messages using Van Dijk’s theory. This type of research is classified as qualitative with the research approach used is analysis. The data source for this research is Ustadz Firanda Andirja Abidin’s video, namely Lentera Hikmah entitled "Emansisapi or Emancipation" on the Ammar TV channel and the data which is considered to have a relationship with the research object. Data analysis techniques used through three stages, namely data reduction, data presentation, drawing conclusions. The results of this study indicate that the da’wah delivered by Ustadz Firanda Andirja is a form of concern when some groups demand justice between men and women, the justice in question is justice for women to do everything on an equal footing with men. Therefore, women and men are free to do whatever they want, but it must still be in accordance with Islamic law.